MOLECULAR CHARACTERIZATION OF Piper retrofractum Vahl IN JAVA USING INTER SIMPLE SEQUENCE REPEATS (ISSR) MARKERS - Sulifah Aprilya Hariyani; Siti Zubaidah (BIOEDUKASI, 2022)
Piper is a genus of the family Piperaceae which has a very large number, in the tropics and sub-tropics. There are about 22 species of Piper which are registered in medicinal herbs and world herbs, one of which is Java chili (Piper retrofractum Vahl.). The morphological characters of P. retrofractum are different in various planting centers, especially the leaf and fruit characters vary. Limitations of morphological characters encourage the use of molecular characters. The purpose of this study was to analyze the molecular character of Java chilli (P. retrofractum) on the island of Java using ISSR (Inter simple sequence repeat) markers. Molecular markers can provide relatively more accurate information because genetic traits tend to be stable in environmental changes and not influenced by age. Leaves from 12 different locations were isolated using the SDS method. Amplification was carried out using 12 ISSR polymers. Data is analyzed using the NTSYS version 2.02 program. The results showed that the amplification of P. retrofractum DNA produced 70 polymorphic DNA bands. The dendrogram results from 12 sampling locations showed that P. retrofractum on Java Island had a similarity coefficient of 0.69-0.93. This shows that genetic diversity based on ISSR markers from P. retrofractum Vahl is relatively low.